Exhibit Russia the new international decade 1986-1996 - Fowle, Kate 1972-; Addison, Ruth (Artguide s.r.o, 2016)
Exhibit Russia is the first publication to reveal how the Russian art scene connected to the rest of the world during the turbulent decade following the adoption of the economic reforms known as perestroika. Focusing on those major group exhibitions and events which jettisoned Russian artists to international attention, or introduced Russian publics to Western art stars, the book provides readers with a unique perspective into the dawning of the global art world. First-hand accounts from leading curators, artists and writers of the time describe the stories behind each exhibition, which are illustrated through rare installation views and archival material. These are accompanied by reprinted articles from magazines, including Flash Art, Art in America and Moscow Art Magazine. The book concludes with a chronology, in which exhibitions are listed in relation to the key historical moments of the decade.